2018
DOI: 10.1021/acs.langmuir.7b03890
|View full text |Cite
|
Sign up to set email alerts
|

Presence of Rigid Red Blood Cells in Blood Flow Interferes with the Vascular Wall Adhesion of Leukocytes

Abstract: The symptoms of many blood diseases can often be attributed to irregularities in cellular dynamics produced by abnormalities in blood cells, particularly red blood cells (RBCs). Contingent on the disease and its severity, RBCs can be afflicted with increased membrane rigidity as seen in malaria and sickle cell disease. Despite this understanding, little experimental work has been conducted toward understanding the effect of RBC rigidity on cellular dynamics in physiologic blood flow. Though many have computati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
37
0
2

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 29 publications
(39 citation statements)
references
References 49 publications
0
37
0
2
Order By: Relevance
“…Microfluidic experiments found a decrease in self-organization in quasi-2D confined flows with decreasing RBC deformability [26]. In vitro work also found that with increasing populations of rigid RBCs in flow reduces the amount of leukocyte adhesion to P-selectin coated substrates [27] and recently to an inflamed endothelium [28]. Previous numerical studies found that the rigid body inside a malaria-infected RBC significantly affects the RBC adhesive dynamics and increases whole blood viscosity [29], as well as the reduction of contact area to the vessel wall in sickled RBCs [30].…”
Section: Introductionmentioning
confidence: 94%
“…Microfluidic experiments found a decrease in self-organization in quasi-2D confined flows with decreasing RBC deformability [26]. In vitro work also found that with increasing populations of rigid RBCs in flow reduces the amount of leukocyte adhesion to P-selectin coated substrates [27] and recently to an inflamed endothelium [28]. Previous numerical studies found that the rigid body inside a malaria-infected RBC significantly affects the RBC adhesive dynamics and increases whole blood viscosity [29], as well as the reduction of contact area to the vessel wall in sickled RBCs [30].…”
Section: Introductionmentioning
confidence: 94%
“…The RBC deformability is crucial to the platelet transport, and the impaired deformability of DRBCs compared to NRBCs may cause weaker platelet margination toward the wall. There is in vitro evidence showing that the presence of rigid RBCs interferes with the WBC recruitment and platelet margination (82,83). In addition, Kumar and Graham have presented a detailed analysis of the segregation mechanism incorporating binary mixtures of capsules with different rigidities by performing a computational study with the boundary integral method (84).…”
Section: Flow Of Healthy and Diabetic Bloodmentioning
confidence: 99%
“…However, even if hyper aggregation and stiffness simultaneously occur, the main effect on the arterial circulation is the presence of rigid RBCs altering the flow, which may affect the function of leukocytes. [90]. Recent studies discuss the effect of rigid cells on margination (movement towards endothelial walls) [91], and results, unfortunately, are not conclusive [92].…”
Section: 1-characteristics Of the Technical Principle Of Rbc Rigidimentioning
confidence: 99%
“…Hundreds of studies [10] and especially numerous new techniques have been proposed to quantify RBC aggregation and deformability, which helps to understand the origin of symptoms of various diseases, including SCA. The quantification of RBC deformability has received increasing attention from researchers [11,12,13,14] and various experimental techniques (filtration, micropipette, ektacytometry, Dientenfass equation based on viscosity and hematocrit values [15,16], etc.) that analyze the deformability-or its inverse, the stiffness of the RBChave been proposed and applied over the last 50 years [17,18,19,20,21,22,23].…”
Section: Introductionmentioning
confidence: 99%